2007
DOI: 10.1007/s00276-007-0258-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of the shoulder and subclavicular innervation by the intermediate and lateral branches of supraclavicular nerves

Abstract: In case of deficiency of these nerves, pain or sensitive deficit can occur without motor trouble. The factors of acute or chronic injury are direct compression, nerve stretching, repetitive stresses, and direct wound. Moreover, several neck or shoulder surgical approaches are dangerous for these nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 5 publications
0
22
0
1
Order By: Relevance
“…The rate of incisional and proximal chest wall numbness has been reported from 10% to 29% after operative treatment of clavicle fractures [2, 20, 21]. The supraclavicular nerve is a superficial sensory nerve that crosses the clavicle and provides sensation over the clavicle, anteromedial shoulder, and proximal chest [5, 8]. In theory, injury to these nerve branches could be reduced by knowledge of their precise location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of incisional and proximal chest wall numbness has been reported from 10% to 29% after operative treatment of clavicle fractures [2, 20, 21]. The supraclavicular nerve is a superficial sensory nerve that crosses the clavicle and provides sensation over the clavicle, anteromedial shoulder, and proximal chest [5, 8]. In theory, injury to these nerve branches could be reduced by knowledge of their precise location.…”
Section: Discussionmentioning
confidence: 99%
“…This nerve arborizes proximal to the clavicle and provides sensation over the clavicle, anteromedial shoulder, and proximal chest [5, 8]. The branching pattern and distances to the nerves from anatomic landmarks at the level of the clavicle are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Supraclavicular (C3 and C4 cervical spinal nerves) and transverse cervical nerves (C2 and C3 cervical spinal nerves) of the cervical plexus are cutaneous branches supplying the periclavicular area and the lower medial part of the neck, including the platysma muscle, respectively. [9][10][11] Sensory innervation of the sternocleidomastoid muscle, including proprioception, arises from C2-C4 cervical spinal nerves. [12][13][14] Accordingly, we hypothesized that an ultrasound-guided (USG) intermediate cervical plexus block (CPB), which targets the posterior cervical space (PCS)between the sternocleidomastoid muscle and prevertebral fascia-as Choquet et al 15 suggested, would effectively treat post-USRM pain associated with both skin incision and sternocleidomastoid muscle resection.…”
mentioning
confidence: 99%
“…However, detailed information about the innervation of the AC joint has only been documented to a limited extent. 9 The aim of this study was to document the pertinent surgical and anatomic relationships of the suprascapular nerve and its branches to the AC joint.…”
mentioning
confidence: 99%